Extract of haruan (channa striata) extract increasing reepithelialization count in wound healing process on wistar rat’s buccal mucosa - Devintha AM. Tamales; Nurdiana Dewi; Lena Rosida (Journal of Dentomaxillofacial Science, 2016)
Haruan is Kalimantan’s indigenous fish which has the potency to accelerate wound healing. Haruan extract has substantial properties such as albumin, Zn, Cu, and Fe to accelerate wound healing. The aim of this study was to examine the effect of haruan extract on reepithelialization of wistar rats’ buccal mucosa wound healing on day 3, 5, 7, and 10 histopathologically. This study was true experimental with posttest with control design. Samples were divided in 16 treatment groups, haruan extract 25%, 50%, 100% treatment groups and aquadest treatment group as negative control, each treatment was performed for 10 days. Epithelial thickness count reached its peak on day 10. Mean epithelial thickness scoring of each group was 50.40 µm; 56.85 µm; 62.81 µm; 38.28 µm respectively. Two way Anova and Post Hoc LSD tests presented there was a significant difference between negative control and haruan extract groups. Haruan extract treatment significantly increases epithelial thickness count in wound healing process.